2017
DOI: 10.56093/ijas.v87i10.74929
|View full text |Cite
|
Sign up to set email alerts
|

Response of wheat (Triticum aestivum) genotypes to different tillage practices for improving productivity and seed quality in eastern Indo-Gangetic plains of India

Abstract: Quality seed, water, labour scarcity, rising cost of cultivation, diminishing farm profits and indecisive weather conditions are major challenges faced by the farmers under intensive tillage based conventional rice-wheat productionsystem of eastern Indo-Gangetic plains (IGP). To address these challenges from last few years, conservation agriculture (CA) based crop management practices are being developed, demonstrated and promoted in the region. The fieldexperiments were carried out during the winter (rabi) se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…It was also found that 50.00 per cent respondents have fully adopted moisture content percentage at the time of harvesting and 20.00 per cent respondents have partially copied the moisture content percentage at the time of harvesting while 30.00 per cent respondents have not adopted the moisture content percentage at the time of harvesting. Similar findings also reported by Ram, et al (2017). The data show that 27.05 per cent wheat growers had low level adoption of improved wheat practices followed by 58.30 per cent respondents having medium level adoption.…”
Section: Resultssupporting
confidence: 86%
“…It was also found that 50.00 per cent respondents have fully adopted moisture content percentage at the time of harvesting and 20.00 per cent respondents have partially copied the moisture content percentage at the time of harvesting while 30.00 per cent respondents have not adopted the moisture content percentage at the time of harvesting. Similar findings also reported by Ram, et al (2017). The data show that 27.05 per cent wheat growers had low level adoption of improved wheat practices followed by 58.30 per cent respondents having medium level adoption.…”
Section: Resultssupporting
confidence: 86%
“…However, ZTFB + R was comparable with it in this regard. Our results are in conformity with the findings of Ram et al, (2017) and Ghosh et al, (2021). As usual, weed-free control due to the highest weed control, resulted in the highest values of plant dry weight (980.0, 985.8 g/ m 2 ), number of ear bearing tillers (359.0, 367.3/m 2 ) and 1,000-grain weight (42.8, 41.7 g).…”
Section: Wheat Growth and Yield Attributessupporting
confidence: 92%